Study the performance of hydrokinetic turbine for home power - Widad, Md. Jamaluddin (2018)
Hydrokinetic Turbine harness energy from low water flow rates instead of using dam and head like conventional turbine. Hydrokinetic Turbine which is Axial Water Turbine designed to support electricity demands for rural area due to limited electricity connection. Small river is the focused which the water flow rate is low and suitable with Axial Water Turbine. The turbine is designed in Siemens NX 10 Nastran in 3D drawing and fabricate start with turbine blades, framework. Voltage generated by turbines range between 4.61V to 5.47V with rotation 1528 rpm and succeeds lighting up 3 bulbs, 1 standing fan with 82.72W suitable with rural area. In the end of this project, several testing has been done on the prototype to measure the efficiency of the turbine.